Basics in Epidemiology & Biostatistics: textbook - Kazmi, W. H. Waqar H. (Jaypee Brothers Medical Publishers, 2015)
Clinical research is a different ball game but is not a rocket science. A lot of young doctors and students tend to get intimidated with epidemiology and biostatistics. The very purpose of this text book is to narrate in a very simple language the basic concepts of epidemiology and biostatistics. The book has placed equal emphasis over both epidemiology and biostatistics part. In the epidemiology portion, attempt has been made to orient the reader with the importance of research, understanding of study design, measures of associations, measures of disease frequency, bias and confounding, concept of screening technique, skills of developing research protocol, data collection, ethical considerations, developing informed consent form and reference writing. In the biostatistics part, the reader will be explained the key concepts of sampling procedure, hypothesis testing, measures of central tendency, variables and data types, sample size estimation and data analysis plan. An attempt has been made to present the information in pictorial and tabular forms, which are easy to understand and retain. Moreover, to clear the concepts multiple examples are given so that the learner could easily understand the key concepts. It has been noted that the postgraduate trainee face difficulty in drafting a research protocol, conducting research and writing a dissertation. Thus, a detailed description of components of Research protocol and dissertation writing has been included in this book.